PENGARUH KRISIS SUBPRIME MORTGAGE AMERIKA SERIKAT TERHADAP PERBANKAN SYARIAH MUAMALAT INDONESIA TAHUN 2006 - 2009 - Kalfi Mahendra; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Has become an obligation a country to advance the economic , By creating regulations and many initiative, To a better economy, And welfare the nation and the country . In each the profitable thing can not be separated of the challenges. Obstacles weakness or disease. So also economic system , also have an impact. And potentially create that delicate problem as the crisis. It cant be denied in this era of globalization currently. national country economy alliance in the world . Starting to show a modern economy competitive . So that trade innternasional be a need for countries in advance economic. United states as a country largest economy in the world. with the gross domestic product (GDP) in 2008 amounted to US $ 14.4 trillion. A quarter of the gross domestic product the world based on nominal and a fifth based on of parity purchasing power.Subprime mortgage crisis fueled by an increase in failed to pay mortgages .And seizure house in the united states . It is a negative impact on banks and global money market . The impact of the crisis in the form of an increase in inflation , the fall in the exchange rate , a decline in the economic growth , The collapse of the market index and a number of banks , institutions , corporate experienced difficulty financial and bankrupt .An impact for indonesia is disruption of the financial and trading channels. And banks had feel their influence . But financial institutions that based syariah especially of the bank muamalat indonesia. Has forbidden flowers in its not too feel the impact of the significant . Bank muamalat indonesia and there is even in terms of loan-to- deposit ratio ( LDR ), Show more liquid than conventional banks in time of crisis global financial happened., It were due to high interest rates.Key words: Subprime Mortgage Crisis, negative impact on banks and global, impact for Indonesia, Bank Muamalat